'n Aantal sosio politieke persepsies van swart jeugdiges in Stedelike gebiede* - Louw, A. D. (Koers, 1989)
In September 1986 a survey was launched among a sample of black youths in metropolitan areas in the R S A in order to obtain a general picture of some of the most important sociopolitical perceptions of this section of South Africa n society. Trained black f ield -worker s used questionnaires to conduct interviews with 372 youths. The respondents ' views were obtained on, inter alia, the following: black education, school boycotts, black unrest, the type of government they would like to have, black and white leadership, the use of violence and negotiation, and their feelings towards other population groups . Most of the youths were in favour of the exis t in g system of authority at schools, disapproved of school boycotts, preferred the police rather than the army to combat crime, disapproved of the unrest in black residential areas and the current state of emergency and p referred a 'democratic government' and negotiation to violence. Most of the black you ths indicated that Mandela was the best ' black leader and also the best leader for South Africa, regarded the ANC as the organization with most support among blacks, considered their feelings towards whites as 'u n change d ' since a year ago, and felt more 'friendly ' towards coloureds and Indians than towards whites.